Fabrication and Stability Study of Multilayer Liposome - GE*, LIQIN; JI, JIANYU (Asian Journal of Chemistry, 2009)
Multilayer nanocapsules were obtained with layer-by-layer (LBL) technique. Liposomes were employed as templates and obtained through extrusion method. The polymers as shells were biocompatible and bio-degradable materials. The obtained multilayer nanocapsules with alginate- chitosan complex were fabricated successfully. The z-potential result confirmed that the different polyelectrolyte layers were absorbed on the liposomes, alternatively. The obtained multilayer liposomes were treated with ethanol [ethanol:water are 1:10 and 1:1 (v/v)] and SDS solution, respectively. The results showed that the obtained capsules were stable to low concentration of ethanol and SDS solution but not stable to high concentration of ethanol solution. Such capsules have potential application in drug delivery system.